Agronomic performance, quality and nitrogen use efficiency by common bean cultivars - Nunes, Hugo Dias [UNESP]; Leal, Fábio Tiraboschi [UNESP]; Mingotte, Fábio Luiz Checchio [UNESP]; Damião, Victor D’Amico [UNESP]; Junior, Pedro Afonso Couto [UNESP]; Lemos, Leandro Borges [UNESP] (Taylor & Francis, 2021)
Nitrogen (N) is the nutrient most required by common bean (Phaseolus vulgaris L.) and the rational management of this element in the crop is very important for increasing the sustainability of agricultural systems. The objective of this study was to evaluate the agronomic performance, qualitative performance and the response and efficiency of N use by 16 common bean cultivars with the commercial grain type “Carioca” in the autumn-winter season under irrigation. The experiment was conducted in a Latossolo Vermelho eutroférrico (Oxisol) under conventional tillage. A randomized block design was used in split plots with four replicates. The plots were consisted of the common bean cultivars: ANFc 9, BRS Ametista, BRS Estilo, BRSMG Madrepérola, Pérola, IAC Alvorada, IAC Imperador, IAC Milênio, IAC Sintonia, IPR Andorinha, IPR Campos Gerais, IPR Tangará, IPR 139 (Juriti Claro), TAA Bola Cheia, TAA Dama and TAA Gol. The subplots comprised the absence and presence of nitrogen (0 and 100 kg ha−1 of N). The agronomic performance of common bean is affected by top-dressing N application, and the cultivars IPR Campos Gerais and IPR Tangará stood out under N application. The common bean cultivars BRS Estilo, IAC Imperador and IPR Campos Gerais are responsive and efficient in the use of N. The qualitative performance of common bean grains is influenced by the top-dressing N application, and the cultivar IAC Alvorada showed the best results. Top-dressing N application increases the protein content and decreases the cooking time of common bean grains.
Keywords: abiotic stress; genotypes; grain technology; grain yield; nitrogen fertilization; Phaseolus vulgaris